HEAD JOLTING NYSTAGMUS: HEAD-SHAKING-INDUCED OCCLUSION OF THE HORIZONTAL SEMICIRCULAR CANAL. Issue 11 (14th October 2015) - Kaski, Diego; Bronstein, Adolfo; Cutfield, Nick; Buckwell, David; Banga, Rupan; Ray, Jaydip; Chavda, Swarupsinh; Irving, Richard
Abstract : Background and aims: We report a new syndrome (head jolting nystagmus, HJN) that expands the differential diagnosis of head-movement induced paroxysmal vertigo. Methods and results: Two male patients (65 and 58 yrs) described rotational vertigo after violent and brief (1–2 s) oscillations of the head (head jolting) that triggered intense horizontal nystagmus lasting 45s. Accelerations of the head required to induce these episodes could only be achieved by the patients themselves. In Patient 1 the episodes gradually disappeared over a 6–year period. In Patient 2, 3–Tesla MRI suggested a filling defect in the left horizontal semicircular canal. He underwent surgical canal plugging that resolved the symptoms. Conclusion and relevance: We attribute HJN to dislodged material within the horizontal semicircular canal, and provide a mechanistic model to explain its origin.